Les aqueducs de Rome : les activités de la Surintendance capitoline, une contribution essentielle à la recherche - Marina Marcelli; Massimiliano Munzi (Gallia)
On 2 October 1847, Pius IX issued the motu proprio “Sull’organizzazione del Consiglio e Senato di Roma e le sue attribuzioni”, which assigned to the Municipality of Rome ownership of the Vergine, Felice and Traiano-Paolo aqueducts along with responsibility for their maintenance. In addition to the Acqua Felice, built by pope Sixtus V (1585-1590), two still functioning Roman aqueducts were concerned: the Aqua Virgo (19 BC), probably the only ancient aqueduct which, flowing mainly in underground channels, has remained in continuous operation to the present day, and the Aqua Traiana (109 AD), which was reactivated by pope Paulus V in 1612.The complexity of these structures, of considerable height and tens of kilometres long, makes monitoring, protection and conservation particularly difficult.This is why the Municipality of Rome, when drawing up the New Master Plan for the city in the 1960s, included the aqueducts as part of the city's protective cultural heritage. An annex to the Plan was dedicated to surveying them: the Carta storica archeologica monumentale e paesistica del suburbio e dell’agro romano. Recently, the elements selected were incorporated into Annex G (the “Carta per la Qualità”) of the New Master Plan, approved in 2008. For the historic aqueducts, the urban planning rules prescribe a 50 m buffer-zone on both sides where all construction is forbidden; if the specus is underground, the buffer zone is 15 m.In 2010 the Sovrintendenza Capitolina, with the support of the service company Zètema Progetto Cultura, initiated a dedicated project to document, analyse and monitor the condition of monumental linear structures and the factors leading to their deterioration, the “Progetto Osservatori”. The targets of this analysis were the City Walls and the aqueducts of the Roman and modern eras. The tool used for this purpose is a Geographical Information System (GIS) designed to collect all the information needed to implement maintenance and conservation activities.The focus of the project was the elevated structures of five aqueducts for a total length of approximately 18 km: Aqua Alexandrina, a Neronian aqueduct on the Caelian Hill, and the three still functioning aqueducts (Aqua Virgo, Aqua Traiana and acquedotto Felice).Carried out by a multidisciplinary team (archaeologists, architects, restorers), the project consisted of assessments of the risk status of the structures based on parameters of various types, such as biological damage, structural and surface degradation, humidity-related phenomena. In addition to natural and environmental causes, anthropogenic factors play a significant role and are often the main cause of structural degradation.By setting standardised parameters relating to the state of preservation and factors of degradation, different levels of risk were attributed, reflecting degrees of urgency. They are allocated different colours on the GIS map, and linked with forms used to evaluate the resources needed for scheduled interventions.A targeted research and restoration project is currently underway on the acquedotto Traiano-Paolo, unique among the aqueducts in that components that capture water from springs near the Bracciano lake basin as well as some 57 km of ancient channels are still functioning.In 2017 the Sovrintendenza, in collaboration with the managing company ACEA ATO2 and with the support of speleo-archaeological organizations, launched a project to explore and study the artefact and map it on a GIS, in order to monitor its state of preservation and to learn more about its complex system of water capture, adduction and redistribution, which is still largely preserved in the original Roman phase.Because of the complexity of the hydraulic system, a “pilot project” was developed to determine the survey and mapping methodologies. A sample site was identified in the zone of the springs near Lake Bracciano, north of Rome. It consists of a section around 1 km long of the main channel in the locality of Vicarello (Trevignano Romano), three complex and fully functioning adduction systems and a fourth abandoned system, all dating from the Roman period. During the explorations, the original spring water capture systems were documented and it was demonstrated that the operations conducted by pope Paul V’s architects to reactivate the aqueduct (1610) involved only some some parts of the aqueduct and the large distribution chambers, known as “botti”. For both the main channel and the adductions, on the other hand, operations were limited to clearing accumulated silt from the abandoned channels along with small restoration activities.